The role of twist on tensile and frictional characteristics of aramid filament yarns (AFYs). (5th February 2021) - Ding, Zuowei; Zhao, Huihui; Hu, Wanjin; Wang, Rui
Abstract: In this study, the role of twist on the tensile and frictional characteristics of aramid filament yarns (AFYs) were systematically studied. The results revealed that the twist is incredibly crucial in optimizing the final properties of AFYs. It was found that the extension at break and the initial modulus had a high rise with the increase of the twist angle. Furthermore, an optimum twist value provided the maximum breaking strength of AFYs. Meanwhile, breaking strength emerged the tendency of enhancement firstly and then descended continuously till to the fracture of AFYs. In addition, it was inferred that the larger the twist angle, the more sharply the aramid filaments were drafted. In conclusion, if reasonably controlled, AFYs will emerge better tensile capability in axial direction, which are significant in actual industry use, especially in the field that sustained destructive power and constant friction.